Patterns of Klebsiella pneumoniae bacteremic dissemination from the lung - Caitlyn L. Holmes; Katherine G. Dailey; Karthik Hullahalli; Alexis E. Wilcox; Sophia Mason; Bridget S. Moricz; Lavinia V. Unverdorben; George I. Balazs; Matthew K. Waldor; Michael A. Bachman (Nature Communications)
Abstract Bacteremia, a leading cause of death, generally arises after bacteria establish infection in a particular tissue and transit to secondary sites. Studying dissemination from primary sites by solely measuring bacterial burdens does not capture the movement of individual clones. By barcoding Klebsiella pneumoniae, a leading cause of bacteremia, we track pathogen dissemination following pneumonia. Variability in organ bacterial burdens is attributable to two distinct dissemination patterns distinguished by the degree of similarity between the lung and systemic sites. In metastatic dissemination, lung bacterial clones undergo heterogeneous expansion and the dominant clones spread to secondary organs, leading to greater similarity between sites. In direct dissemination, bacterial clones exit the lungs without clonal expansion, leading to lower burdens in systemic sites and more dissimilarity from the lung. We uncover bacterial and host factors that influence the dynamics of clonal sharing and expansion. Here, our data reveal unexpected heterogeneity in Klebsiella bacteremia dynamics and define a framework for understanding within-host bacterial dissemination.